1976
DOI: 10.1093/genetics/83.4.645
|View full text |Cite
|
Sign up to set email alerts
|

MUTATOR ACTIVITY OF PETITE STRAINS OF SACCHAROMYCES CEREVISIAE

Abstract: Petite strains in Saccharomyces exhibit enhanced spontaneous mutation rates of nuclear genes regardless of whether they are cytoplasmically or nuclearly inherited, or whether or not the cytoplasmic petite strains have mitochondrial DNA. In petite strains, the mutation rate for the nonsense allele lys1-1 is enhanced by a factor of 3-6 and for the missense allele his1-7 by a factor of 2 as compared with their grande counterparts. The reversion of a third allele, the putative frameshift mutation, hom3-10, is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…in Werner syndrome), both resulting in defective structural maintenance and repair of the genome 2 . Intriguingly however, in yeast, increased nuclear genome instability in respiration-deficient mutant strains was reported already in the 1970s 3 . A later study found a similar response as a consequence of chemical inhibition of cellular respiration 4 .…”
Section: Introductionmentioning
confidence: 99%
“…in Werner syndrome), both resulting in defective structural maintenance and repair of the genome 2 . Intriguingly however, in yeast, increased nuclear genome instability in respiration-deficient mutant strains was reported already in the 1970s 3 . A later study found a similar response as a consequence of chemical inhibition of cellular respiration 4 .…”
Section: Introductionmentioning
confidence: 99%